ANALYSIS OF THE CURRENT STATE OF RUSSIAN-CHINESE COOPERATION IN THE SPHERE OF ENERGY AND ITS DEVELOPMENT PROSPECTS - Ma Hang (Статистика и экономика)
Oil and gas resources are the main energy resources consumed in the world, so the oil and gas industry has the economic and political aspects, profoundly inuencing the development of modern international economic and political relations.This article analyzes the current state of Russian-Chinese cooperation in the sphere of energy resources on the basis of statistical data on the volume of bilateral trade and energy compared with the data of other countries exporting energy resources. Also assessed the prospects for Russian-Chinese cooperation in the sphere of energy resources on the background of signicant world events and the Sino-Russian relations over the last few years (for example, the impact on the Russian-Chinese cooperation events such as rising US energy independence and solutions IMF to include the yuan in the basket SDR).